Enamel erosion by commercial ice tea and kombucha in vitro - Mähönen, Hilma (My University, 2022)
This in vitro study aimed to evaluate the erosive potential of commercially available ice tea and kombucha beverages. Ice teas are known to have low pH and often contain added acids e.g. citric acid. Fermentation process and added acids make tea based kombuchas acidic but the erosive potential has not been much studied. Critical pH for enamel dissolution is often considered to be 5.5 but other factors such as fluoride may modify the erosion process. Fluoride is known to increase enamel remineralisation and to prevent demineralisation. This in vitro study included 25 commercial ready-to-drink tea based beverages of which 15 were ice teas and 7 were kombuchas. Water was used as negative control and cola drinks as positive controls. Fluoride concentration and pH of each beverage was measured. Calcium release from hydroxyapatite in each beverage was measured to simulate dissolution of enamel. Enamel specimens form extracted bovine teeth were exposed to selected beverages for 1 hour and the specimens were analysed with scanning electron microscopy (SEM) to demonstrate effects on enamel surface. Out of 25 studied beverages 22 had higher release of calcium from hydroksyapatite than the cola drinks (p-value < 0.05). All studied beverages had pH lower than 5.5. The kombuchas had lower pH (2.82-3.66) than the ice teas (2.94-4.86). Fluoride concentrations of the beverages were low (0.03-0.46 ppm). All enamel surfaces showed etching patterns confirming the surface changes in SEM images. The results suggest high erosive potential of ice teas and especially kombuchas.
Keywords: enamel erosion, ice tea, kombucha